Rapid determination of caine-based anesthetics and their metabolite residues in fish using a modified QuEChERS method coupled with UPLC-MS/MS - Shouer Lin; Wenqian Qiu; Yongyou Hua; Yan Yang (Food Chemistry: X)
Caine-based anesthetics are frequently used in the production and transportation of aquatic products, but residues in fish threaten human health. A rapid, sensitive, and effective method was developed for detecting caine-based anesthetics and their metabolite residues in fish using ultra-high performance liquid chromatography-tandem mass spectrometry coupled with a modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) method. The sample was extracted with 0.05 % (v/v) formic acid-80 % acetonitrile, 4 g NaCl was added for liquid partitioning, and 50 mg C18 was used for purification. Matrix-matched calibrations showed good correlation coefficients with R2 ≥ 0.9942. The limits of detection were 0.5–4.4 ng/g. The recoveries ranged from 71.4 %–115.8 %, and the relative standard deviation for intra-day and inter-day precision was less than 8.5 % and 9.2 %, respectively. This method effectively analyzed the residues of caine-based anesthetics and their metabolites in fish and could be applied to aquatic product anesthetic regulation.